Perceived Discrimination and Aggression Among Chinese Migrant Adolescents: A Moderated Mediation Model - Xiong, Ruoshan; Xia, Yiwei; Li, Spencer D. (Frontiers in Psychology, 2021)
Previous research has showed that Chinese rural-to-urban migrant adolescents are at high risk for discrimination, negative emotions, and aggression. However, little is known about how discrimination, negative emotions and aggression are interrelated and whether social support addressing the emotional needs of the adolescents would moderate the relationship of discrimination to aggression. This study attempts to fill these gaps. Based on prior research, it is proposed that perceived discrimination relates to reactive aggression by increasing negative emotions that foster aggressive responses to stressful events. Considering the central role that negative emotions may play, it is also hypothesized that socioemotional support provided by family, friends and community mitigates the impact of perceived discrimination on reactive aggression by reducing negative emotions. The results obtained from the analysis of two-wave survey data collected from a probability sample of 470 migrant students aged 11-17 (46.17% female; mean age=13.49) in China supported these hypotheses. The findings indicate that perceived discrimination fosters negative emotions, which in turn increase reactive aggression. Additionally, socioemotional support reduces the adverse impact of perceived discrimination on reactive aggression by weakening the link between perceived discrimination and negative emotions. Practical and policy implications of these findings are discussed.